PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FACE WASH BIORE DI KOTA SEMARANG - Kirania Putri Basti; Dinalestari Purbawati; Andi Wijayanto (Universitas Diponegoro, 2024)
Beauty products become increasingly popular among consumers in recent times, this trend extends to products Face Wash. Skincare brands work diligently to maintain their established Brand Image, includes highlighting the excellence of their product ingredients, competitive pricing strategies, and precise targeting in their promotional efforts. The quality of a company's offerings also plays a crucial role in consumers' evaluations. This research to investigate the influence of brand image and product quality on the purchasing decisions of Biore Face Wash in Semarang. The research adopts an Explanatory Research approach, utilizing a nonprobability sampling method and purposive sample selection. The study involves 100 respondents who are users of Biore Face Wash in Semarang City. Data collection is conducted online through the use of Google Forms. The research employs analyses such as validity testing, reliability testing, correlation coefficient analysis, determination coefficient analysis, simple linear regression, multiple regression, t- test, and F-test with the assistance of SPSS software version 26. The research findings reveal that there is a significant influence of brand image on purchasing decisions, a significant influence of product quality on purchasing decisions, and a significant combined influence of both brand image and product quality on the purchasing decisions of Biore Face Wash users.Keywords: brand image; product quality; buying decisionProduk kecantikan merupakan produk yang akhir-akhir ini sangat populer di kalangan konsumen, termasuk Face Wash. Brand skincare harus dapat mempertahankan Brand Image yang telah dimilikinya seperti keunggulan ingredients yang dimiliki oleh produk, penetapan harga yang dapat bersaing, dan promosi yang tepat pada target sasaran. Kualitas pada sebuah produk yang ditawarkan oleh perusahaan juga menjadi penilaian konsumen. Penelitian ini bertujuan untuk mengetahui pengaruh brand image dan kualitas produk terhadap keputusan pembelian Biore Face Wash di Kota Semarang. Tipe penelitian yang digunakan adalah Explanatory Research dengan teknik pengambilan menggunakan metode nonprobability sampling dan purposive sample. Penelitian ini menggunakan 100 responden pengguna Biore Face Wash di Kota Semarang. Pengumpulan data dilakukan secara online dengan menggunakan google form. Dan penelitian ini menggunakan analisis uji validitas, reliabilitas, koefisien korelasi, koefisien determinasi, regresi linear sedehana, regresi berganda, uji t, dan uji F dengan bantuan software SPSS versi 26. Hasil penelitian menunjukkan bahwa terdapat pengaruh brand image terhadap keputusan pembelian, terdapat pengaruh kualitas produk terhadap keputusan pembelian dan terdapat pengaruh antara brand image dan kualitas produk terhadap keputusan pembelian pengguna Biore Face Wash.Kata Kunci: citra merek; kualitas produk; keptutusan pembelian